2016
DOI: 10.1007/s00264-016-3253-9
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of measurements performed on two dimensional and three dimensional computed tomography in glenoid assessment for instability

Abstract: Purpose The main purpose of this study is to establish which of two methods is more reliable in glenoid assessment for instability in pre-operative planning. Accordingly, we have studied the intra-and inter-observer reliability of glenoid parameters with the use of two-dimensional (2D) and three-dimensional (3D) reconstructed computed tomography (CT) images. Methods One hundred glenoids were measured with the use of 2D-CT and 3D-CT (in 3D orientation) by two independent observers (one experienced and one inexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…We have been able to show in our previous study that 3D glenoid reconstruction is more reliable for glenoid bone loss assessment than 2D [14]. Therefore, we have focused on the measurement of humeral head defects in shoulder instability.…”
Section: Introductionmentioning
confidence: 99%
“…We have been able to show in our previous study that 3D glenoid reconstruction is more reliable for glenoid bone loss assessment than 2D [14]. Therefore, we have focused on the measurement of humeral head defects in shoulder instability.…”
Section: Introductionmentioning
confidence: 99%
“…Bishop et al 44 demonstrated MRI to be less reliable than CT. 44 Bois et al 28 demonstrated poor reliability for 2-dimensional CT measurements. Kubicka et al 29 determined 2-dimensional CT to be less reliable than 3-dimensional CT, which they attributed to differences in plane of cut that are overcome by our study design. Markenstein et al 35 demonstrated MRI to be reliable for the assessment of glenoid bone loss.…”
Section: Discussionmentioning
confidence: 72%
“…[25][26][27] In addition, they can be performed on both 2-dimensional CT slices and 3-dimensional osseous scapular reconstructions with subtraction of the humeral head to allow an en face view. [28][29][30][31] As CT involves radiation and additional cost, there has been significant interest in determining whether these measurements could be made accurately and reliably using magnetic resonance imaging (MRI) alone. 29,[31][32][33][34][35][36][37][38] Driven by this interest, 3dimensional MRI reconstructions also have become available.…”
Section: See Commentary On Page 20mentioning
confidence: 99%
See 2 more Smart Citations